Screening of Non-Conventional Yeasts on Low-Cost Carbon Sources and Valorization of Mizithra Secondary Cheese Whey for Metabolite Production - Gabriel Vasilakis; Rezart Tefa; Antonios Georgoulakis; Dimitris Karayannis; Ioannis Politis; Seraphim Papanikolaou (BioTech)
The production of microbial metabolites such as (exo)polysaccharides, lipids, or mannitol through the cultivation of microorganisms on sustainable, low-cost carbon sources is of high interest within the framework of a circular economy. In the current study, two non-extensively studied, non-conventional yeast strains, namely, Cutaneotrichosporon curvatus NRRL YB-775 and Papiliotrema laurentii NRRL Y-3594, were evaluated for their capability to grow on semi-defined lactose-, glycerol-, or glucose-based substrates and produce value-added metabolites. Three different nitrogen-to-carbon ratios (i.e., 20, 80, 160 mol/mol) were tested in shake-flask batch experiments. Pretreated secondary cheese whey (SCW) was used for fed-batch bioreactor cultivation of P. laurentii NRRL Y-3594, under nitrogen limitation. Based on the screening results, both strains can grow on low-cost substrates, yielding high concentrations of microbial biomass (>20 g/L) under nitrogen-excess conditions, with polysaccharides comprising the predominant component (>40%, w/w, of dry biomass). Glucose- and glycerol-based cultures of C. curvatus promote the secretion of mannitol (13.0 g/L in the case of glucose, under nitrogen-limited conditions). The lipids (maximum 2.2 g/L) produced by both strains were rich in oleic acid (≥40%, w/w) and could potentially be utilized to produce second-generation biodiesel. SCW was nutritionally sufficient to grow P. laurentii strain, resulting in exopolysaccharides secretion (25.6 g/L), along with dry biomass (37.9 g/L) and lipid (4.6 g/L) production.